2011
DOI: 10.12660/joscmv4n1p1-12
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Logistics Performance: the Effectiveness of Mmog/Le as Perceived by Suppliers in the Automotive Industry

Abstract: In spite of logistics having grown in importance lately, which included the discussion of concepts such as integrated logistics and supply chain management in the business agenda, little has been discussed about how to measure logistics performance. This paper analyzes the perception of logistics professionals about the effectiveness of MMOG/LE (Materials Management Operating Guideline/Logistics Evaluation), which is a set of recommendations regarding logistics and materials management that was created by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…They differ from most cases abroad, which are mainly focused on acts of terrorism and natural disasters. Some Brazilian resilience research includes: Graeml and Peinado (2014), Pereira et al (2014) and Sá et al (2020). Among these and other papers from the international literature, studies that detail the role of cross-functional integration on resilience are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They differ from most cases abroad, which are mainly focused on acts of terrorism and natural disasters. Some Brazilian resilience research includes: Graeml and Peinado (2014), Pereira et al (2014) and Sá et al (2020). Among these and other papers from the international literature, studies that detail the role of cross-functional integration on resilience are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience management in the supply chain is a recent research theme, which also features introductory studies in Brazil such as Graeml and Peinado (2014), Pereira et al (2014), Sá et al (2020). Consequently, we opted for a qualitative approach through a case study that allows answering questions such as “how” and “why,” based on abundant empirical evidence (Yin, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…The findings in [10] revealed that the effectiveness of logistics operations has an impact on the organization's overall performance. Multiple studies support top managers' comments that they attribute improved customer service, inventory levels, and cost to better logistics, indicating that this is a fair generalization.…”
Section: Performance Measurementmentioning
confidence: 99%
“…Involving customers in finding solutions for these challenges is helpful in continually updating the drivers of customer perceived value of logistics (Yazdanparast et al , 2010). Dimensions of service quality have been adapted to logistics services by some authors in the past (Taşkin and Durmaz, 2010; Graeml and Peinado, 2011; Wilding and Juriado, 2004; Yazdanparast et al , 2010). “Assurance” is a perceived dimension where the logistics service provider guarantees that the goods would be delivered to the desired location without any damage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A monitoring system will allow assessing and making decisions on resources allocation and process improvement as per customers’ expectation. Efficiency in logistic activity also has an impact on customer perceived value (Graeml and Peinado, 2011). High value to customer is a key factor for creating and maintaining long-term customer–supplier relationships (Fiol et al , 2009).…”
Section: Literature Reviewmentioning
confidence: 99%